产出导向法在国际中文教育中的应用研究现状与发展趋势 - Yue Jiang; Chili Li (Sinolingua: Journal of Chinese Studies, 2026)
Production-Oriented Approach (POA) is an important research achievement in second language education. Its application to international Chinese education can promote the localization of second language teaching concepts and improve the quality of international Chinese teaching. To understand its research trends and development direction, it is necessary to review the research in this field. By searching the China National Knowledge Infrastructure (CNKI) database, 58 relevant papers on the use of POA in the field of international Chinese education over the past decade (2015–2025) were collected. Based on the scoping review method and using CiteSpace visualization software, the development status and trends were analyzed. The study found: 1) the overall development of POA in international Chinese education has experienced considerable fluctuations, roughly divided into two stages with 2019 as the node: the initial stage and the rapid development stage; 2) research hotspots mainly include three aspects: POA teaching practice research, technology empowerment and teaching innovation, and teaching material adaptation and development. These findings are implicative for improving teaching quality of International Chinese Language Education.